Defining evidence-based nursing practice: An interpretative phenomenological study - Cheung, Kartian Ka Chun; Su, Jing Jing; Batalik, Ladislav (Nurse education today, 2025)
BACKGROUND: Evidence-based nursing practice (EBNP) has been regarded core competencies in nursing practice and education. Defining evidence-based nursing practice and translating evidence into nursing practice by nursing students who are green to clinical practice in their education journey remain unclear. AIM: To explore how pre-registered nursing students define and characterize evidence-based nursing practice as they participate in their clinical practicum. DESIGN: This study used an interpretive phenomenological qualitative study design. SETTINGS AND PARTICIPANTS: Twenty nursing students were interviewed for their clinical practicum experience from four universities, one nursing college and one hospital-based nursing school in Hong Kong. METHODS: Data was generated through semi-structured in-depth interview and analyzed following interpretative phenomenological analysis guidelines, using a cyclical coding process. RESULTS: Four themes emerged regarding nursing students' definition of EBNP, highlighting that EBNP is 'identifying a reliable learning source', by which they can 'rationalize their nursing practice', and enabling them to 'establish care standard through critical thinking', and eventual 'fostering their professionalism' to improve health outcomes and reduce potential harms. CONCLUSION: Nursing students defined and characterized evidence-based nursing practice as core competencies in accompany their practicum that enables them to learn and grow professionally with a universal desire to be qualified, cope with doubt, and improve patient outcome. They recognized the challenges in identifying evidence and emphasized conservative approach to validate the evidence to avoid patient harm. Students expressed doubt towards their instructors EBNP when observing procedures untaught at school, which requires the curriculum model to foster students' skills in applying and appraising evidence and instructors' capacity to rationalize and role model EBNP.
Keywords: Interviews as Topic; klinické kompetence; Evidence-based practice; Evidence-Based Nursing; Hong Kong; mužské pohlaví; Adult; Clinical Competence; Interpretative phenomenological study; Education, Nursing, Baccalaureate; kvalitativní výzkum; Students, Nursing; ženské pohlaví; Qualitative Research; Humans; Nursing students; studium ošetřovatelství bakalářské; rozhovory jako téma; ošetřovatelství založené na důkazech; Hongkong; Qualitative research; dospělí; Clinical practicum; Female; lidé; Male; studenti ošetřovatelství